2018
DOI: 10.1101/gad.309245.117
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis controls phosphate homeostasis

Abstract: Phosphorus is an essential element assimilated largely as orthophosphate (Pi). Cells respond to Pi starvation by importing Pi from their surroundings. We now report that impaired protein synthesis alone triggers a Pi starvation response even when Pi is plentiful in the extracellular milieu. In the bacterium serovar Typhimurium this response entails phosphorylation of the regulatory protein PhoB and transcription of PhoB-dependent Pi transporter genes and is eliminated upon stimulation of adenosine triphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 84 publications
4
76
2
Order By: Relevance
“…We do not know the mechanisms by which MgtS and PitA impact PhoRB activity. Interestingly, low Mg 2+ was recently found to activate the PhoRB response in S. enterica due to low free cytoplasmic phosphate levels brought about by decreased protein synthesis associated with reduced ATP consumption, though induction of the reporter construct was only observed after 120 min (Pontes and Groisman, ). Independent of the mechanisms, we followed up our observation that MgtS acts through PitA to test the effect of different MgtS alleles and explore the consequences for growth on low Mg 2+ .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We do not know the mechanisms by which MgtS and PitA impact PhoRB activity. Interestingly, low Mg 2+ was recently found to activate the PhoRB response in S. enterica due to low free cytoplasmic phosphate levels brought about by decreased protein synthesis associated with reduced ATP consumption, though induction of the reporter construct was only observed after 120 min (Pontes and Groisman, ). Independent of the mechanisms, we followed up our observation that MgtS acts through PitA to test the effect of different MgtS alleles and explore the consequences for growth on low Mg 2+ .…”
Section: Resultsmentioning
confidence: 97%
“…PhoR is converted to its kinase state, thereby mimicking low phosphate conditions and resulting in the activation of the PhoRB regulon. Consistent with this, it was recently found that low intracellular Mg 2+ in Salmonella enterica strains lacking Mg 2+ transporters led to induction of the PhoRB regulon (Pontes and Groisman, ). It also is interesting to note that mutations in pitA , mgrB and phoQ all were found in screens for long‐term adaptation to the antibiotic trimethoprim in LB medium (Baym et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Microbial Biotechnology published by John Wiley & Sons Ltd and Society for Applied Microbiology, Microbial Biotechnology, 11, 588-605 phosphate uptake by the Pst system (Brokaw et al, 2017). Interestingly, impairing translation triggers a phosphate starvation response (Pontes and Groisman, 2018). A plausible conjecture is therefore that PhoU is an enzyme, producing yet another metabolite, presumably containing phosphate, that interferes with homeostasis of phosphate metabolism associated with the ATP control of translation, perhaps via translation throttle EttA (Boel et al, 2014).…”
Section: Abduction: Extracting Information From Phenotypesmentioning
confidence: 99%
“…This process reduces electrostatic repulsion among Pi groups in the rRNA backbone, enabling the folding and assembly of functional ribosomes. Not accidentally, ATP and rRNA constitute the largest cytoplasmic reservoirs of Pi and Mg 2+ (9,11,(13)(14)(15)(16)(17)(18). Given this inherent connection between Pi and Mg 2+ , we wondered if cytotoxic effects of excessive Pi uptake result from its assimilation into ATP and subsequent disruption of Mg 2+ dependent processes in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%